Juridical Analysis In Overcoming Obstacles To The Development Of Individual Companies In The Digital Era - Nicholas Tjenggana; M. Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The Indonesian state is a state based on law (rechstaats) not a state based on force or arbitrariness. Therefore, everything related to state activities from an economic, political, social and cultural perspective will be regulated by law. This research uses an empirical juridical research method using qualitative techniques and the approach method used in this research is a statutory approach and a conceptual approach using literature studies and interviews. The promulgation of the Job Creation Law and Government Regulation Number 8 of 2021 concerning the Authorized Capital of Companies and Registration of Establishment, Changes and Dissolution of Companies which have requirements for UMK are currently known, namely that an Individual Company can be established by 1 person. Obstacles: Individual companies must comply with complex regulations related to data privacy, consumer protection and taxes in the digital era. Solution: Have a strong understanding of applicable regulations and ensure internal systems and processes comply with required compliance standards. Regularly update policies and procedures to ensure ongoing compliance.